Observation of initial clinical manifestations and repercussions from the treatment of 314 human injuries caused by black sea urchins (Echinometra lucunter) on the southeastern Brazilian coast - Vidal Haddad Junior (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: Injuries caused by sea urchins are the most common caused by marine animals in humans in Brazil, with the black sea urchin (Echinometra lucunter) causing the most injuries to bathers. METHODS: This study observed 314 human wounds with emphasis on the early observation of clinical signs and symptoms and their implications on the recommended treatment. RESULTS: All the injuries were caused by black sea urchins and were observed in bathers. The lesions and the pain were associated with penetration of the spines; there was no early inflammation or pain without pressure on the wounded places. Complications arising from this kind on injury, including infections and foreign body granulomas, are associated with the permanence of the spines in the wounds. CONCLUSIONS: The study confirmed that this kind of injury is the most common accident caused by aquatic animals in Brazil. The main therapeutical recommendation is early removal of the spines to prevent late complications, such as infections and the formation of foreign body granulomas.